Auditory performance and speech intelligibility results in children with cochlear implants - (:unkn) unknown (My University, 2003)
Objective: The aim of this study was to evaluate auditory performance and speech perception of congenitally deaf children after implantation. Methods: The study consisted of 24 prelingually deafened children with cochlear implants (CI). Auditory performance and speech intelligibility after cochlear implantation were assessed using two scales: Speech Intelligibility Rating (SIR) and the Categories of Auditory Performance (CAP). Results: The auditory performance and speech intelligibility of all children increased after implantation. CAP and SIR results of the children who were implanted before the age of four, who used hearing aids before implantation and who had strong family support were superior to the group of children implanted after the age of 4, who did not used hearing aids and who did not have family support. Conclusion: All children participated to the study benefited from cochlear implant in terms of increase of auditory performance. As the time of CI usage increases, speech intelligibility also increases. Intelligibility becomes significant by the end of third year of CI use. Strong family support, use of CI and early implant age are found to be important for succes with CI.
Keywords: Auditory Performance; Children; Cochlear implant; Speech intelligibility